2016
DOI: 10.1021/acs.molpharmaceut.6b00226
|View full text |Cite
|
Sign up to set email alerts
|

Positively Charged Surface-Modified Solid Lipid Nanoparticles Promote the Intestinal Transport of Docetaxel through Multifunctional Mechanisms in Rats

Abstract: Solid lipid nanoparticles (SLNs) are one of the most promising nanocarriers to increase the oral absorption of drugs with poor solubility and low permeability. However, the absorption mechanism of SLNs remains incomplete and thus requires further careful consideration. In this study, positively charged chitosan (CS) modified SLNs or hydroxypropyl trimethylammonium chloride chitosan (HACC) modified SLNs were designed and their absorption mechanisms were fully clarified to improve the oral absorption of docetaxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 37 publications
(57 reference statements)
2
31
0
Order By: Relevance
“…[188][189][190][191][192] A recent study with docetaxel showed that HACC-modified chitosan administered orally exhibits a higher drug bioavailability via various absorption mechanisms including transcellular, paracellular and M cell uptake. 193 Interestingly, the study also found that HACC-modified SLNs showed a higher uptake of the drug in the Peyer's Patches than normal cells. The same research group also showed that HACC-modified SLNs with a uniform particle size achieved enhanced bioavailability with around 2.45 times increase of the drug through oral delivery.…”
Section: Hydroxypropyl Trimethyl Ammonium Chloride Chitosan (Hacc)-momentioning
confidence: 84%
“…[188][189][190][191][192] A recent study with docetaxel showed that HACC-modified chitosan administered orally exhibits a higher drug bioavailability via various absorption mechanisms including transcellular, paracellular and M cell uptake. 193 Interestingly, the study also found that HACC-modified SLNs showed a higher uptake of the drug in the Peyer's Patches than normal cells. The same research group also showed that HACC-modified SLNs with a uniform particle size achieved enhanced bioavailability with around 2.45 times increase of the drug through oral delivery.…”
Section: Hydroxypropyl Trimethyl Ammonium Chloride Chitosan (Hacc)-momentioning
confidence: 84%
“…Several factors were suggested in previous studies to elaborate the possible mechanism(s) underlying enhancement of the oral bioavailability of a drug when loaded into nanocarriers. For instance, studies reported that SLNs could enter the lymphatic circulation and are further transferred to systemic circulation via two possible mechanisms: (i) microfold cells (M cells) uptake nanoparticles in the Peyer’s patches; and (ii) paracellular and/or transcellular uptake SLNs [ 22 , 25 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that incorporation of drugs into SLNs might alter their intestinal permeability following oral administration. Drugs that are encapsulated into SLNs could gain access to the systemic circulation via the lymphatic system through M cells of Peyer’s patches found in the ileum [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Table 3 , select LNS examples and their delivered drugs based on BDDCS class are presented to demonstrate their mechanistic strategies of improving oral bioavailability [ 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ]. By taking advantage of existing physiological characteristics of the small intestines, the following six strategies have the potential to use nanoparticle (NPs) formulations to address intestinal CYP3A4 metabolism and to enhance the absorption of drugs and NPs across enterocytes: (1) incorporating mucoadhesive polymers or lipids that are attracted to the unstirred water layer adjacent to the intestinal epithelia, allowing drugs to be in close proximity which increases the flux into epithelial cells to overwhelm CYP3A4 metabolism; (2) CYP3A4 inhibitor-containing LNS locally inhibits intestinal CYP3A4 during transcytosis; (3) using highly lipophilic lipid NPs to traverse enterocytes straight into lymphatic vessels; (4) formulating LNS targeting M cell integrins for endocytosis that carries the drug to lymphatic vessels; (5) pH-sensitive formulation that selectively releases drug in the ileum where there is a lower expression of intestinal CYP3A4; (6) vitamin B12 targeting cubilin in the terminal ileum for absorption via receptor mediated endocytosis.…”
Section: Lns Strategies Of Overcoming Pre-systemic Cyp3a4 Metabolismmentioning
confidence: 99%